Legionella RavZ Plays a Role in Preventing Ubiquitin Recruitment to Bacteria-Containing Vacuoles - Kubori, Tomoko; Bui, Xuan T.; Hubber, Andree; Nagai, Hiroki (Frontiers in Cellular and Infection Microbiology, 2017)
Bacterial pathogens like Salmonella and Legionella establish intracellular niches in host cells known as bacteria-containing vacuoles. In these vacuoles, bacteria can survive and replicate. Ubiquitin-dependent selective autophagy is a host defense mechanism to counteract infection by invading pathogens. The Legionella effector protein RavZ interferes with autophagy by irreversibly deconjugating LC3, an autophagy-related ubiquitin-like protein, from a phosphoglycolipid phosphatidylethanolamine. Using a co-infection system with Salmonella, we show here that Legionella RavZ interferes with ubiquitin recruitment to the Salmonella-containing vacuoles. The inhibitory activity is dependent on the same catalytic residue of RavZ that is involved in LC3 deconjugation. In semi-permeabilized cells infected with Salmonella, external addition of purified RavZ protein, but not of its catalytic mutant, induced removal of ubiquitin associated with Salmonella-containing vacuoles. The RavZ-mediated restriction of ubiquitin recruitment to Salmonella-containing vacuoles took place in the absence of the host system required for LC3 conjugation. These observations suggest the possibility that the targets of RavZ deconjugation activity include not only LC3, but also ubiquitin.